Analysis of Junior High School Students’ Learning Outcomes on the Concept of Heat and Its Changes - Hamid, Fatma; Sahjat, Sumarni; Sehe, Nurjana D; Limatahu, Iqbal; Rahman, Nurdin Abd; Widyasari, Halleyna; Saprudin, Saprudin (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
Students’ learning outcomes in the topic of heat and its changes are often limited by difficulties in understanding and analyzing thermal concepts. This study aims to analyze students’ learning outcomes based on four cognitive indicators: remembering (C1), understanding (C2), applying (C3), and analyzing (C4), as well as to identify individual student performance through two rounds of testing. This research used a descriptive quantitative approach involving 30 seventh-grade students, with six students selected as subjects for deeper analysis. Data were obtained through written tests administered twice and analyzed descriptively. The results showed that students achieved very good performance in the remembering indicator (95%) and good to very good performance in the understanding (75%) and applying indicators (80%). However, performance in the analyzing indicator remained low (60%), indicating that students’ higher-order cognitive skills are not yet adequately developed. Individual analysis further showed that most students fell into the fair category. The novelty of this study lies in the combined use of indicator-based and individual learning outcome analyses with repeated measurements, allowing a clearer picture of students’ cognitive strengths and weaknesses. Overall, these findings highlight the need for learning strategies that promote analytical thinking to improve student outcomes in the topic of heat and its changes.